THE IMPACT OF LANGUAGE IN THE TEACHING AND LEARNING OF MATHEMATICS AT JUNIOR SECONDARY SCHOOL IN KATSINA - ABUBAKAR, HAMZA; UMAR, SANI ABUBAKAR; MUSAWA, BASIRU IBRAHIM (IJRDO -JOURNAL OF MATHEMATICS, 2015)
The purpose of this research was to determine the effect of Language on Junior Secondary students’ academicperformance in mathematics. Participants were 120 students, purposefully sampled among Junior Secondaryone (JSSI) students of Government Science Secondary School Dutsin-Ma, Katsina in Nigeria. Data collectionoccurred before and after proper teaching(in Hausa) for 12 weeks. two research question were formulated toguide this study. The statistical analysis showed there was a significant difference before and after theteaching in Hausa on students Performance in Mathematics (p≤ 0.05). Based on the findings, it wasrecommended among the other things that home Language (mother-tongue) should be adopted in our schoolsystem particularly at Junior secondary schools in Nigeria as it will improve students’ performance inMathematic towards sustainable development in Nigeria